Development of non-loaded test protocols for fire ratings of different building components in a vertical furnace - Pascual, Genarro Rafael
Case studies of possible fire testing that can be done with the UP Diliman Ice Furnace are categorized into: Material Testing, Fire Resistance Rating Tests and Smoke Testing. From the case studies, list standards for the fire resistance rating testing of doors are shortlisted (British Standard, International Organization for Standardization, American Society for Testing and Materials, National Fire Protection Association, and Japanese Industrial Standards), and a list of furnace recommendations is presented. The equipment of the furnace is checked on whether or not they suffice for each standard. An equipment checklist is also populated should all the standards be implemented, taking into account equipment parallels between standards. Finally, another equipment checklist is provided should two standards be simultaneously used in testing. The fire resistance protocol is the collection of all the considered standards in this research, supplanted by testing methodologies found in several case studies. Smoke testing procedures are also provided. Finally, the calibration of the furnace, which includes repeatability and reproducibility check of a calibration test, as well as provisions for thermocouple calibration are presented.